Inverse Kinematics of a New Quadruped Robot Control Method. (16th January 2013) - RunBin, Cai; YangZheng, Chen; Lin, Lang; Jian, Wang; Xu, Ma Hong
Design of redudant joints has been widely used in quadruped robots, so new kinds of techniques for sloving inverse kinematics are needed. In this paper we propose a new control method called Time-Pose control method and choose the enhanced extended jacobian matrix method for inverse kinematics. We deduce extended jacobian matrix method again so that it can be applicable for arbitrary joint length. It is argued that because the method can generate close joint angle path. With Time-Pose control method, such kind of inverse kinematics method has been used for trot gait on the flat ground. Simulations and experiments are performed, which prove the extended jacobian matrix method to be realizable for the quadruped robot.